Development of Fluorescent Carbon Nanoparticle-Based Probes for Intracellular pH and Hypochlorite Sensing - Yu-Syuan Lin; Li-Wei Chuang; Yu-Feng Lin; Shun-Ruei Hu; Chih-Ching Huang; Yu-Fen Huang; Huan-Tsung Chang (Chemosensors, 2022)
Acid-base and redox reactions are important mechanisms that affect the optical properties of fluorescent probes. Fluorescent carbon nanoparticles (CNPs) that possess tailored surface functionality enable a prompt response to regional stimuli, offering a useful platform for detection, sensing, and imaging. In this study, mPA CNPs were developed through one-pot hydrothermal reaction as a novel fluorescent probe (quantum yield = 10%) for pH and hypochlorite sensing. m-Phenylenediamine was chosen as the major component of CNPs for pH and hypochlorite responsiveness. Meanwhile, ascorbic acid with many oxygen-containing groups was introduced to generate favorable functionalities for improved water solubility and enhanced sensing response. Thus, the mPA CNPs could serve as a pH probe and a turn-off sensor toward hypochlorite at neutral pH through fluorescence change. The as-prepared mPA CNPs exhibited a linear fluorescence response over the pH ranges from pH 5.5 to 8.5 (R2 = 0.989), and over the concentration range of 0.125–1.25 μM for hypochlorite (R2 = 0.985). The detection limit (LOD) of hypochlorite was calculated to be 0.029 μM at neutral pH. The mPA CNPs were further applied to the cell imaging. The positively charged surface and nanoscale dimension of the mPA CNPs lead to their efficient intracellular delivery. The mPA CNPs were also successfully used for cell imaging and sensitive detection of hypochlorite as well as pH changes in biological systems. Given these desirable performances, the as-synthesized fluorescent mPA CNPs shows great potential as an optical probe for real-time pH and hypochlorite monitoring in living cells.